2022
DOI: 10.3390/diagnostics12123141
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers for Laboratory Diagnostics of Atherosclerosis—Literature Review

Abstract: Atherosclerosis is still considered a disease burden with long-term damaging processes towards the cardiovascular system. Evaluation of atherosclerotic stages requires the use of independent markers such as those already considered traditional, that remain the main therapeutic target for patients with atherosclerosis, together with emerging biomarkers. The challenge is finding models of predictive markers that are particularly tailored to detect and evaluate the evolution of incipient vascular lesions. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 148 publications
0
1
0
Order By: Relevance
“…Currently, there are several serum markers used to identify early AS, such as lipoproteins, ceramides, C-reactive proteins, high-sensitivity C-reactive proteins, matrix metalloproteinases, and miRNAs, among which high-sensitivity C-reactive proteins are comprehensively validated in the prediction of atherosclerotic cardiovascular events 45 47 . In our study, we identified six Hub genes for AS, and the nomogram demonstrated satisfactory diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several serum markers used to identify early AS, such as lipoproteins, ceramides, C-reactive proteins, high-sensitivity C-reactive proteins, matrix metalloproteinases, and miRNAs, among which high-sensitivity C-reactive proteins are comprehensively validated in the prediction of atherosclerotic cardiovascular events 45 47 . In our study, we identified six Hub genes for AS, and the nomogram demonstrated satisfactory diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%